Flow characteristic investigation on Laval-type flow rate regulating valves by fluid-thermal-structure interaction. (May 2023) - Zhang, Yayun; Peng, Jinghui; Li, Songjing
Abstract: The flow characteristics are of great significance for flow rate regulating valves (FRRVs) to regulate the mass flow rate of gas and avert excessive energy consumption. Nevertheless, the deformation of fluid-thermal-structure interaction (FTSI) is an impact factor affecting the flow characteristics, which is usually neglected by convention numerical calculations, but can be captured by FTSI numerical calculations. In this work, the Laval structure is proposed to improve the flow characteristics of FRRVs. Numerical studies of FTSI and convention are performed to analyze the flow characteristics of the valve. Based on these numerical calculations, the pressure and velocity distribution characteristics are presented and the temperature, stress, heat exchange, and deformation of FTSI are analyzed. Meanwhile, characteristics of mass flow rate with pressure are evaluated by linear fitting method, and the polynomial fitting method is utilized to capture the characteristics of mass flow rate with valve spool opening. Experimental investigations are also carried out for verification. Compared with experimental data, FTSI numerical results show a good agreement with errors less than 4.974% but the convention numerical ones give relatively larger deviations of 20.64%. The results reveal that the proposed FTSI numerical method is more precise and reasonable for predicting the flow characteristics of FRRVs in engineering. Highlights: Laval structure was proposed in the FRRV to improve flow characteristics. Model of fluid-thermal-structure interaction for Laval-type FRRV was established. Characteristics of mass flow rate upon pressure were evaluated by linear fitting method. Characteristics of mass flow rate upon valve spool opening were evaluated by polynomial fitting method.